An efficient identity-based signature protocol over lattices for the smart grid - Longzhu Zhu; Fan Jiang; Min Luo; Quanrun Li (High-Confidence Computing, 2023)
As the promising next-generation power grid, the smart grid has developed rapidly in recent years. The smart grid enables energy to be stored and delivered more efficiently and safely, but user data’s integrity protection has been an important security issue in the smart grid. Although lots of digital signature protocols for the smart grid have been proposed to resolve this problem, they are vulnerable to quantum attacks. To deal with this problem, an efficient identity-based signature protocol on lattices is proposed in this paper. To improve our protocol’s efficiency, the tree of commitments is utilized. Moreover, a detailed performance evaluation of the proposed protocol is made. The performance analysis demonstrates that the potential utility of our protocol in the smart grid is huge.